Measuring Long-Run Expectations that Correlate with Investment Decisions - Peter Haan; Chen Sun; Georg Weizsäcker; Felix Weinhardt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2025)
Different methods of eliciting long-run expectations yield data that predict economic choices differently well. We ask members of a wide population sample to make a 10-year investment decision and to forecast stock market returns in one of two formats: they either predict the average of annual growth rates over the next 10 years, or they predict the total, cumulative growth that occurs over the 10-year period. Results show that total 10-year forecasts are more pessimistic than average annual forecasts, but they better predict experimental portfolio choices and real-world stock market participation.
Keywords: D01; D14; D84; D9; 330; Household finance; long-run predictions; survey experiments